TYPES OF IMPLICATURE IN INFORMAL CONVERSATIONS USED BY THE ENGLISH EDUCATION STUDY PROGRAM STUDENTS - Endry Sri Rahayu Sri Rahayu; Safnil . (Universitas Bengkulu, 2016)
Implicature was refers to implied meaning in utterance that can be understood by indirectly expression. In informal conversation was occurred the hidden meaning of what actually said by the speakers. This study was investigated the types of implicature in informal conversations used by the English education study program students. The study was aimed to analyze the types of implicature and how the implicature is carried out in the informal conversations. The method of study was a descriptive qualitative method. The subjects of this study were 25 students of English study program who have informal conversation. The students’ conversation was transcribed and analyzed by using checklist instrument. The results was shown that 1) there were three types of implicature found in the informal conversations; conventional implicature, generalized conversational implicature and particularized conversational implicature, and 2) the implicature is carried out in the informal conversations by the used of generalized conversational implicature and particularized conversational implicature. Moreover, a conclusion is students in the informal conversation have potentially implicature that indicates that their utterance has implied meaning. The suggestions, the study about implicature should be conducted in different area such as movie, drama or others, to give enrichment information in the Pragmatics study.